STUDI KOMPARASI MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA SMK KELAS X PADA PENERAPAN PEMBELAJARAN DARING DI ERA PANDEMI COVID-19 - Astriyanti, Anita; Rejeki, Sri (Pendidikan Matematika UNIMOR, 2022)
The Covid-19 pandemic is an extraordinary event that is currently hitting various parts of the world. Many of the consequences caused by this outbreak of this virus. Limitation of social interaction (social distancing) in an effort to break the chain of the spread of Covid-19 was taken and followed government health protocols. Online learning as an alternative to learning in the midst of the Covid-19 pandemic. Learning that is carried out indirectly and is in a network, of course, makes students must have strong learning motivation to achieve maximum learning outcomes. There are two objectives in this study, namely 1) to analyze and test the differences in learning outcomes of class X students of SMK Muhammadiyah Kartasura in offline learning before the Covid-19 pandemic era and in online learning in the Covid-19 pandemic era, 2) Analyze and test the influence of motivation on outcomes. class X student of SMK Muhammadiyah 1 Kartasura in online learning in the Covid-19 pandemic era. This research uses a quantitative approach with the type of comparative causal research. The results of this study indicate that there are significant differences in the average learning outcomes of Class X Vocational School students in offline learning before the Covid-19 pandemic era and in online learning in the Covid-19 pandemic era. Student learning outcomes in offline learning are higher than in online learning. Meanwhile, the one-way Anova test results show that there is an influence of motivation on learning outcomes of class X Vocational High School students in online learning in the era of the Covid-19 pandemic. Students have high motivation to learn in the high and low groups.